2020
DOI: 10.1371/journal.pgen.1008588
|View full text |Cite
|
Sign up to set email alerts
|

Loss of androgen signaling in mesenchymal sonic hedgehog responsive cells diminishes prostate development, growth, and regeneration

Abstract: Prostate embryonic development, pubertal and adult growth, maintenance, and regeneration are regulated through androgen signaling-mediated mesenchymal-epithelial interactions. Specifically, the essential role of mesenchymal androgen signaling in the development of prostate epithelium has been observed for over 30 years. However, the identity of the mesenchymal cells responsible for this paracrine regulation and related mechanisms are still unknown. Here, we provide the first demonstration of an indispensable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The intrauterine microenvironment plays a pivotal role in physiologic embryonal development including prostate development, growth and potential predisposition to the PCa later on in life [39]. Using a rat model of maternal exposure to lowprotein diet, an impaired prostatic growth associated with prostate carcinogenesis in older offspring has been demonstrated [40].…”
Section: Imbalanced Maternal Diet and Abnormal Embryonic Developmentmentioning
confidence: 99%
“…The intrauterine microenvironment plays a pivotal role in physiologic embryonal development including prostate development, growth and potential predisposition to the PCa later on in life [39]. Using a rat model of maternal exposure to lowprotein diet, an impaired prostatic growth associated with prostate carcinogenesis in older offspring has been demonstrated [40].…”
Section: Imbalanced Maternal Diet and Abnormal Embryonic Developmentmentioning
confidence: 99%
“…The majority of PCs are associated with defective DNA damage repair molecules, while androgen receptor (AR) signaling also plays an important role in PC pathogenesis, particularly in metastasized cases ( 187 ). During fetal life, the AR and SHH pathways play a crucial role in the development of the prostate gland ( 188 , 189 ). Le et al ( 188 ) reported that, during prostate development, growth and regeneration, both pathways are indispensable; the AR signaling pathway is superior since, in the murine in vivo model, the expression of AR was essential for urogenital mesenchymal and epithelial cell differentiation, even if the cells overexpressed GLI1 .…”
Section: Shh Pathway In Cancers Of the Male Reproductive Systemmentioning
confidence: 99%
“…007909) [ 27 ] mTmG mice (stock No. 007676) [ 32 ] Lac Z (b-D-galactosidase) (NC_000913) Escherichia coli mmu-miR-770-5p, mmu-miR-770-3p, mmu-miR-767, mmu-miR-1906, mmu-miR-203b-3p, mmu-miR-122-3p, mmu-miR-3071-3p, mmu-miR-7011-3p, mmu-miR-6372,mmu-miR-214-3p, mmu-miR-615-3p, mmu-miR-761 R26R mice (stock No. 003474) [ 25 ] Z/EG transgenic mice (stock No.…”
Section: Discussionmentioning
confidence: 99%